Identification and characterization of screen use trajectories from late childhood to adolescence in a US-population based cohort study - Iris Yuefan Shao; Joanne Yang; Kyle T. Ganson; Fiona C. Baker; Jason M. Nagata (Preventive Medicine Reports, 2023)
Screen use is a known risk factor for adverse physical and mental health outcomes during childhood and adolescence. Moreover, racial/ethnic disparity in screen use persists among adolescents. However, limited studies have characterized the population sharing similar longitudinal patterns of screen use from childhood to adolescence. This study will identify and characterize the subgroups of adolescents sharing similar trajectories of screen use from childhood to adolescence.Study participants of the Adolescent Brain Cognitive Development Study (2016–2021) in the U.S with non-missing responses on self-reported screen use at each year of the study were included in the analysis. Growth mixture modeling was used to identify the optimal number of subgroups of adolescents with similar trajectories. Subsequently, socio-demographic characteristics, familial background, and perceived racism and discrimination during childhood was assessed for each subgroup population. Perceived discrimination was measured using the Perceived Discrimination Scale.There were two major subgroups of individuals sharing similar trajectories of screen use: Drastically Increasing group (N = 1333); Gradually Increasing group (N = 10336). Higher proportions of the Drastically Increasing group were racial/ethnic minorities (70%) as compared to the Gradually Increasing group (45%). Moreover, the Drastically Increasing group had higher proportions of individuals reporting perceived racism and discrimination during childhood.